Meningkatkan Ketahanan Korosi dan Daya Rekat Menggunakan Powder coating dan Cat Liquid pada Proses Coating Lapisan Logam - Sudarto, Sudarto; Firmanto, Bayu; Rahman Oktaviansyah, Aulia; Amin Mansur, Ahmad (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
Industrial applications widely employ powder coating to shield products from corrosion. Effective anti-corrosion coatings enhance customer satisfaction, open new markets, and withstand temperature, abrasion, and chemicals. However, powder coating and liquid paint remain options to mitigate metal damage. Corrosion behavior of coated materials exposed to strong acids was investigated to understand the influence of liquid/powder coatings and HCl/H2SO4. This study evaluated the corrosion resistance of A0-BS3 metal specimens coated with powder (AC1-AS3) and liquid (BC1-BS3) coatings against HCl and H2SO4 solutions for 7 days. Corrosion rates were calculated and compared, and surface damage was analyzed. Corrosion occurred in all materials in HCl and H2SO4. H2SO4 exhibited 25 times faster corrosion, and coatings were ineffective. Powder coating outperformed liquid paint. Acid rain can damage liquid paint. Powder coating is the preferred choice. Ongoing research aims to enhance steel corrosion resistance, compare coatings, and assess long-term effects. This study contributes significantly to combating corrosion and developing more effective and environmentally friendly anti-corrosion solutions.